Solutions for the pollinators of agro-industrialcrops - Savchenko, A. (ТДАТУ, 2018)
EN: The article presents a brief information about of production of biological means for the processing of agro-industrial crops and the problem of poisoning pollinators - colonies of bees and other beneficial insects, which affected the large quantitative reduction in the amount of honey obtained. The main objective of this article is to summarize information on existing Bayer works in the field of processing of plant raw materials and the protection of plant pollinators from the deadly ingredients used by the company Bayer and other world-leading companies in this field of economy. UK: В тезах представлена коротка інформація про виробництво біологічних засобів для переробки агропромислових культур та про проблему отруєння запилювачів - колоній бджіл та інших корисних комах, які вплинули на значне кількісне скорочення кількості отриманого меду. Основною метою цієї статті є узагальнення інформації про існуючі роботи компанії Bayer у галузі обробки рослинної сировини та захисту рослин-запилювачів від смертельних інгредієнтів, що використовуються компанією Bayer та іншими світовими компаніями у цій галузі економіки.
Keywords: проблема отруєння запилювачів; бджоли; захист рослин-запилювачів; problem of poisoning pollinators-colonies; colonies of bees